The in-store shopping experience: A comparative study of supermarket and clothing store customers - N. S. Terblanche; C. Boshoff (South African Journal of Business Management, 2004)
Various developments continually pressurise retailers to find new and innovative ways to differentiate themselves from competitors and adapt to ever-changing and accelerating environmental circumstances. Positioning based on customers' in-store shopping experience (ISE) offers retailers an alternative means of differentiation and is achieved by providing a superior in-store shopping experience. The ISE instrument that has been developed to measure customers' in store shopping experience is used in this study to compare the in-store shopping experiences of customers of two diverse retailing environments (supermarkets versus clothing retailers) by assessing its impact on customer retention. A proposition is formulated and the findings reported. The implications of ISE and customer retention for retail managers are also dealt with.
Keywords: 650